How China’s vocational education formed its distinctive system: a five-element integration theory perspective - Zhu, Guoping; Zhu, Guohua; Baylon, Jay (Frontiers in Education, 2025)
Throughout the ages, a vocational education system with international influence must be supported by a distinctive industrial market, a strong organization, and a standardized and orderly education standard. The modern vocational education system with Chinese characteristics has experienced the embryonic form of technical colleges centered on primary vocational education (1949–1991), the semi-systematic state centered on secondary vocational education (1991–2012), the establishment of the system centered on higher vocational education (2012–2019), and the construction of the modern vocational education system with Chinese characteristics that highlights types of education Standing and sound (2019 to date) and other four stages. The reason why China’s vocational education can form its own system needs to be explained by Chinese local theories. The Five-Element Integration Theory holds that the leadership of the party is unique and the core. The Ministry of Education is the standard setter for vocational education; Schools, including all kinds of vocational education schools at all levels, are the concrete implemutors of training standards; Enterprises and industry associations have the right to set demand standards to a certain extent; The student body is the center of vocational education and the object of vocational talent training. Through international comparison, China’s vocational education system is a standardized public platform relative to the one, two, three yuan of the main dimension and the students or enterprises of the core concern dimension.